The Prospects of Development of the Innovative Clusters in St. Petersburg - Aleksandr Isaakovich Maizel (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In spite of the economic globalization the geographic location of a company retains one of the main factors of the competitiveness. This phenomenon is connected with the formation of territorial clusters including industrial enterprises, R&D organizations, educational institutions, and state agencies. The article deals with the clusters formed in St.Petersburg by now. The problems, specific, and general structure of the innovative clusters in the educational sphere is considered.